Approximation by Bézier Variant of Baskakov-Durrmeyer-Type Hybrid Operators - Lahsen Aharouch; Khursheed J. Ansari; M. Mursaleen (Journal of Function Spaces)
We give a Bézier variant of Baskakov-Durrmeyer-type hybrid operators in the present article. First, we obtain the rate of convergence by using Ditzian-Totik modulus of smoothness and also for a class of Lipschitz function. Then, weighted modulus of continuity is investigated too. We study the rate of point-wise convergence for the functions having a derivative of bounded variation. Furthermore, we establish the quantitative Voronovskaja-type formula in terms of Ditzian-Totik modulus of smoothness at the end.